Hypothyroidism consequent to thyroidectomy is associated with elevated remnant lipoproteins and cholesterol enrichment of triglyceride-rich lipoproteins: an observational study - Adrian Post; Mirthe H. Links; Wouter T. Zandee; Margery A. Connelly; Thera P. Links; Robin P. F. Dullaart (Lipids in Health and Disease)
Abstract Background Hypothyroidism may affect triglyceride-rich lipoprotein (TRL) subfractions and low-density lipoprotein (LDL) and their averaged sizes. The present study aimed to determine whether increases in remnant particles were larger than other TRL subfractions and whether changes in remnant particles were related to changes in the TRL cholesterol/triglyceride ratio. Methods An observational study was conducted to assess the impact of short term (4–6 weeks) hypothyroidism consequent to thyroidectomy on TRL subfractions, including remnant lipoproteins, LDL subfractions, and the TRL cholesterol and triglyceride content. Seventeen patients were studied: (1) during hypothyroidism, 4–6 weeks after total thyroidectomy for differentiated thyroid carcinoma (thyroid stimulating hormone (TSH) ranging from 59 to 371 mU/L) and free thyroxine (ranging from 0.8 to 6.8 pmol/L) and (2) after approximately 20 weeks of thyroid hormone supplementation, aimed at TSH levels below the reference range (TSH ranging from 0.01 to 2.15 mU/L). TRL, LDL subfractions, and the cholesterol and triglyceride content in TRL were measured by nuclear magnetic resonance spectroscopy. Results Hypothyroidism led to substantial increases (> 30%, p < 0.001) in total cholesterol, LDL cholesterol, non-HighDensity Lipoproteins, triglycerides, TRL particle concentrations, and LDL particle concentrations. Among TRL subfractions, very small TRL particles (24–29 nm), corresponding to remnant lipoproteins, showed the most pronounced reduction (59%, 95% confidence interval (CI): 70–45%) after thyroid hormone supplementation (P < 0.001). TRL cholesterol content and the TRL cholesterol/triglyceride ratio were also higher during hypothyroidism (P < 0.001). Changes in TRL cholesterol correlated with changes in very small TRL particles (r = 0.70, 95% CI: 0.34–0.88, P = 0.002). Conclusions Profound hypothyroidism confers increases in TRL and LDL particles, with the most pronounced effect on very small TRL (remnant) particles. These effects on remnants coincide with an increase in TRL cholesterol and the TRL cholesterol/triglyceride ratio. Trial registration number NTR ID 7228, 20-08-2018.